LEGAL ANALYSIS OF THE APPLICATION OF CRIMINAL PENALTIES FOR PERPETRATORS OF NARCOTICS CRIMES - Jon Heder Depari; Herny Aspan; T. Riza Zarzani (International Journal of Synergy in Law, Criminal, and Justice, 2026)
This study discusses the legal status and application of criminal penalties for perpetrators of narcotics crimes from the perspective of Law Number 35 of 2009 concerning Narcotics, with a focus on implementation in the Kabanjahe Detention Center. Narcotics are basically legally recognized only for health purposes and the development of science, but in social practice they are often misused, giving rise to multidimensional problems. The law has formulated criminal provisions in Chapter XV Articles 111 to 148, which divide narcotics crimes into four main categories: possession, production and distribution, trade or intermediary, and carrying and transporting. From each of these categories, criminal sanctions are determined with different levels of severity, including provisions for rehabilitation for addicts and victims of abuse. The study results indicate that there is tension between the law on the books and the law in action. Normatively, Article 112 paragraph (1) stipulates a minimum sentence of four years for possession of class I narcotics without permission, but in practice, there are court decisions that impose lighter sentences, such as Supreme Court Decision Number 3790 K/Pid.Sus/2020. This indicates the flexibility of judges in considering the status of abusers, whether as perpetrators of criminal acts or as victims who deserve rehabilitation. The implementation of criminal law at the Kabanjahe Detention Center includes admitting inmates, executing prison sentences, and providing guidance and rehabilitation programs. However, limited facilities and human resources prevent rehabilitation from being optimal. This study emphasizes the need for a balance between repressive law enforcement and humane rehabilitation efforts to effectively achieve the goals of protecting the community and rescuing victims of drug abuse.